Pengaruh Struktur Modal, Ukuran Perusahaan, Pertumbuhan Pendapatan, Dan Loan To Deposit Ratio Terhadap Kinerja Perusahaan Perbankan (Studi Empris Perusahaan Perbankan Terdaftar di Bursa Efek Indonesia Periode 2010 2014) - Alfadin, Muh. Arfan Dwi, Dr. Triyono, SE.,MSi (2016)
This study aimed is to analyze the effect of capital structure, company size, growth, and loan to deposit ratio (LDR) of the company's performance. The population in this study are all banking companies listed on the Indonesia Stock Exchange 2010-2014. The sample in this study were selected using purposive,sampling method. The sample used in this study are 155 companies. In this study, the data was tested by using classic assumption test, multiple regression, T-test and F test. The results showed that the variables of capital structure has effect on company's performance, size company's has no effect the company's performance, growth has effect on company's performance, and loan to deposit ratio (LDR) has no effect the company's performance.